Menguji Kembali Pemikiran Yusuf Al-Qardawi dalam Penentuan Awal Bulan Hijriah - ABDUL MUFID (Universitas Islam Negeri Fatmawati Sukarno, 2020)
This study explores and criticizes the views of Yusuf al-Qardhawi in determining the beginning of the Islamic month. Based on several valid hadiths, Yusuf al-Qaradawi is of the view that the determination of the beginning of the Hijri month can be carried out by three methods, namely rukyat (observation), hisab (astronomical calculations), and istikmal. Therefore, the fundamental question that will be examined in this paper is how is Yusuf al-Qaradawi's view when clarified by the study of hadith and astronomical studies? The main source for Muslims in understanding Islamic teachings is the Koran and Hadith. For Muslims, the Hadith second ranks after the Koran. Throughout Islamic history, hadith is a source of controversy in Islamic law. Among the problems that are still warm and almost always occur today is an understanding of the observations of the crescent related to the determination of the beginning of the Islamic month. Questioning about the differences in determining the beginning of the Hijri month is the result of different perspectives to understand the hadith about crescent observations. Therefore, the method of understanding the hadith about